Inheritance and Tourism Development of Miao Silver Jewelry Forging Skills in Western Hunan - Fu, Peixi (International Journal of Social Sciences and Public Administration, 2024)
As an important part of China’s intangible cultural heritage, the silver forging skills of the Miao nationality in western Hunan have unique historical and cultural values. However, with the acceleration of the modernization process, traditional skills are facing the dilemma of inheritance fault and market shrinkage. Through literature research and field investigation, this paper analyzes the inheritance status of the silver forging skills of the Miao nationality in western Hunan and its application in tourism development and explores the balance strategy between protection and development. The study found that although tourism development has brought new opportunities for silver forging skills, there are still problems such as single product and insufficient market promotion. This paper proposes strategies such as improving product diversity, strengthening brand building, and enhancing tourists’ participation experience. In combination with the theory of sustainable development, it proposes an innovative protection and development model. Through digital technology and creative design, the inheritance and development of silver forging skills can be further promoted, hoping to provide a theoretical basis and practical guidance for the sustainable development of the silver forging skills of the Miao nationality in western Hunan.